Analisis Pengaruh Variabel Makroekonomi terhadap Inflasi di ASEAN-5 : (Indonesia, Thailand, Philipina, Malaysia dan Singapura) - Panji Adekantari; Syamsul Amar (Universitas Negeri Padang, 2022)
The aims the research to analyze the effect of macroeconomics to inflation in ASEAN-5. This research used panel data for the period 2009-2019 taken from World Bank, ASEAN Statistics and International Financial Statistics (IFS). This research uses panel data regression analysis with economic growth, narrow money, broad money and exchange rates as independent variables and inflation as the dependent variable. The results of this research showed the variables of economic growth and broad money have a positive and significant effect on the inflation in ASEAN-5. Besides, the variable of narrow money has a negative and significant effect on the inflation in ASEAN-5. While the exchange rate variable has a positive but not significant effect on the inflation in ASEAN-5.